Alcohol consumption and the risk of renal cancers in the European prospective investigation into cancer and nutrition (EPIC). Issue 8 (28th April 2015) - Wozniak, Magdalena B.; Brennan, Paul; Brenner, Darren R.; Overvad, Kim; Olsen, Anja; Tjønneland, Anne; Boutron‐Ruault, Marie‐Christine; Clavel‐Chapelon, Françoise; Fagherazzi, Guy; Katzke, Verena; Kühn, Tilman; Boeing, Heiner; et al.
<x xml:space="preserve">Abstract</x> Epidemiologic studies have reported that moderate alcohol consumption is inversely associated with the risk of renal cancer. However, there is no information available on the associations in renal cancer subsites. From 1992 through to 2010, 477, 325 men and women in the European Prospective Investigation into Cancer and Nutrition cohort were followed for incident renal cancers (n = 931). Baseline and lifetime alcohol consumption was assessed by country‐specific, validated dietary questionnaires. Information on past alcohol consumption was collected by lifestyle questionnaires. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated from Cox proportional hazard models. In multivariate analysis, total alcohol consumption at baseline was inversely associated with renal cancer; the HR and 95% CI for the increasing categories of total alcohol consumption at recruitment versus the light drinkers category were 0.78 (0.62–0.99), 0.82 (0.64–1.04), 0.70 (0.55–0.90), 0.91 (0.63–1.30), respectively, (ptrend = 0.001). A similar relationship was observed for average lifetime alcohol consumption and for all renal cancer subsites combined or for renal parenchyma subsite. The trend was not observed in hypertensive individuals and not significant in smokers. In conclusion, moderate alcohol consumption was associated with a decreased risk of renal cancer.